90Y-TheraSpheres: The New Look of Yttrium-90. (May 2019) - Arnold, Christina A.; Pezhouh, Maryam K.; Lam-Himlin, Dora; Pittman, Meredith E.; VandenBussche, Christopher; Voltaggio, Lysandra
Abstract : Selective internal radiation therapy with 90 Y-TheraSphere or 90 Y-SIRSphere is used in the treatment of unresectable hepatic malignancies. To the best of our knowledge, this is the first 90 Y-TheraSpheres series. BTG International Canada Inc. provided nonradiated microspheres from the Nordion manufacturer. The histologic processed microspheres were colorless, refractile, polarizable, 20 to 30 μm in diameter, and an occasional internal bulls'-eye seen with the condenser out and an internal cross seen with polarized light. Identical microspheres were identified in 15 hepatectomy specimens from four centers between February 2016 and March 2018. The patients were usually male (male=10, female=5) with a mean age of 59 years. All patients had a prior diagnosis of hepatocellular carcinoma (HCC) and documented 90 Y-TheraSphere (mean duration from last deployment=32 wk). All surgical pathology specimens in these 15 patients were reviewed, but the microspheres were only identified in the hepatectomy specimens. During manuscript preparation, one case of 90 Y-TheraSpheres gastritis was prospectively identified from a separate patient with a history of HCC and 90 Y-TheraSpheres. In conclusion, recognition of 90 Y-TheraSpheres is important so that one may consider the possibility of a nearby malignancy and or establish the cause of the background inflammatory or radiation-related injury. These structures can be easy to miss because the subtle morphology is distinct from previously reported 90 Y-SIRSphere. Clues to the diagnosis include a history of HCC and background radiation change. We report the characteristic morphology as microspheres that overlap in size with 90 Y-SIRSphere, but can be differentiated based on 90 Y-TheraSpheres' colorless appearance with occasional internal bulls'-eyes with the condenser out and an internal cross with polarized light.